Kajian Masalah Kewangan yang dihadapi Kontraktor Bumiputera Semasa Fasa Pembinaan - Abdullah, Hanif; Sarpin, Norliana; Omar, Roshartini; Mohamed, Sulzakimin; Ismayatim, Norddin (Research in Management of Technology and Business, 2021)
The Malaysian government has introduced several policies in increasing the economic dominance of the Bumiputera in Malaysia. Among the government's actions in this matter is to give specific government contracts to Bumiputera contractors only. But unfortunately, some Bumiputera contractors fail to last long in the construction industry in Malaysia due to financial problems. Therefore, the objective of this study is to identify the financial problems often faced by Bumiputera contractors during the construction phase, examine the factors of strong capital absence when starting construction work among Bumiputera contractors and suggest appropriate methods in improving the financial performance of Bumiputera contractors in the construction industry. The methodology of this study is qualitative method with the use of interview as instrument for data collection. Meanwhile, the scope of this study involves three Bumiputera contractor firms based in the state of Johor. The data collected were analyzed using content analysis. The results of the study found that the main financial problem faced by Bumiputera Contractors is the low liquidity of the firm. In addition, the study also found that unqualified contractors are a major factor in the lack of strong capital when starting construction work. Therefore, several suggestions have been identified in improving the financial performance of Bumiputera Contractors including to segregate company accounts and personal accounts. It is hoped that this study can benefit Bumiputera Contractors as well as increase the achievement of Bumiputera in the construction industry in Malaysia.